Aspek Maslahah-Mudharat Terhadap Pelegalan Ganja Sebagai Obat Perspektif Hukum Islam - Syam, Sherina; Musyahid, Achmad; Jamil (Universitas Islam Negeri Alauddin Makassar, 2022)
This article discusses about the aspects of maslahah harm against pelegalan cannabis as a drug in the perspective of islamic law. Pernelitian using this type of library research using the techniques of analysis. By using this approach, the study of normative-juridical. As for the source of the data used, namely: primary data and secondary data. Data processing method that uses the analysis of the content, i.e. to explain and analyze the data that have been found or observed. The results of this study indicate that 1) Maslahah in accordance with the understanding that: each of the everything that is beneficial to humans. While the harm that is something that can be detrimental to self or others and should be left alone when not in a state of dharurat, 2) Which became the basis pelegalan marijuana as a drug that the presence of some consideration by the state-state related benefits of marijuana. Therefore, in the UN Convention of the recommendations of the WHO, the united nations issued a cannabis from class IV to class I, which means Narcotic type of cannabis is legalized in the purposes of treatment, 3) in Terms of the rules of Islamic Law Cannabis equated or by analogy with the wine that is haraam because the same can be intoxicating for its users, there are opinions of scholars that there are scholars who remain forbidden even though as a drug and there are also allow. Scholars who forbid marijuana as a medicine because it argues that cannabis has more loses than maslahahnya, whereas that allow because in a state of dharurat for medical purposes. From the aspect of maslahah and the harm of marijuana, cannabis have much more beneficial compared to mudhratnya, not only in terms of aspects of health but also in terms of economic aspects, construction, and others. The implications of this research are: 1) People need to know more about the maslahah and harm of various aspects in order not to be abused, especially for the youth need education about the marijuana both in terms of religion and norms there. 2) As muslims in got information should really seek out the source of the clear order not to be mistaken in the understanding of maslahah and the harm of cannabis.